Occupational sensitization to epoxy resins in Northeastern Italy (1996–2010). (January 2015) - Prodi, Andrea; Rui, Francesca; Fortina, Anna Belloni; Corradin, Maria Teresa; Filon, Francesca Larese
<x content-type="archive" xml:space="preserve">Abstract</x> Background: One of the main health concerns of epoxy resins is their role as skin sensitizer. This sensitization is not uncommon, because the prevalence ranges around 1–12% of the general population. Objectives: Perform a cross sectional study in a patch test population from Northeastern Italy to investigate the prevalence of epoxy resins sensitization among patients with suspected contact dermatitis. Subsequently, relate findings to patients' occupation and evaluate time trend of prevalence. Methods: The final study database included 19 088 consecutive patients, tested from 1996 to 2010 in Northeastern Italy. Results: The overall prevalence of epoxy resins sensitization was 0·89%. Dermatitis most frequently involved hands (40·25%). In both sexes, we find a significant correlation in mechanics, woodworkers, and chemical industry workers; and in males only, among farmers and fishers, construction workers, and unemployed. We found significant increase of sensitization in construction workers in the analyzed period. Conclusions: The overall prevalence of sensitization to epoxy resins in Northeastern Italy is in line with other European countries, but we found an increased risk of sensitization in some professions and an increasing trend of prevalence in construction workers. Better preventive actions are strongly advised in higher risk professions, with particular attentions towards building sector.